Training On the Use of Google Form for Learning Assessment in Elementary School During the Covid 19 Pandemic - Sendi Fauzi Giwangsa; Nana Jumhana; Arie Rakhmat Riyadi; Ruswandi Hermawan; Evi Rahmawati; Ari Arasy Magistra; Rahmania Mutiara Sari; Anisa Nurul Fadhilah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The existence of the COVID-19 pandemic has made the learning process that was originally face-to-face to online distance learning. One aspect that is still not optimal is in the assessment of learning. There are many applications that can be used by teachers in the implementation of online learning assessments. One of the online assessments that is often used is google form. This google form platform has been widely used for online assessments such as for blinding evaluation exercises, evaluating lecturers' performance and for alternative learning evaluations. The method implemented in this training is training through the zoom meeting application and also assignments. This training is aimed at elementary school teachers. The number of participants for this training is 10 elementary school teachers from Sumedang, Bandung, Cimahi, and West Bandung areas. This training consists of three stages, namely training preparation, training implementation, and post-training control. In general, the results of the training are in accordance with the tutorials given during the training, starting from the identity page, entering questions, entering answer keys and scoring. Based on the results of the questionnaire given after the training, 95% of the respondents received a positive response. The participants responded that the training carried out was very useful and relevant to the needs of the online learning period.